Research in logistics service quality: a systematic literature review - Kilibarda, Milorad; Andrejić, Milan; Popović, Vlado (Transport, 2020)
Logistics Service Quality (LSQ) is recognized as an important tool in modern markets. In recent years, a number of researches in this field are growing rapidly. Numerous papers have been published in various industries and observation focuses. Different methods have been applied with a large number of dimensions. However, there are no papers in literature that provide a systematic review of researches in the observed area. This paper aims to investigate, systematize and analyse relevant papers dealing with the LSQ. The purpose of this paper is to form a systematic review of the different approaches, dimensions and focuses of measurement, analysis and improvement of the logistics services quality. The authors conducted systematic literature review to research papers published in academic journals. Different key words have been used for paper research in several databases. According to research question and defined criteria papers selection has been performed. The relevant group of papers is further investigated in more details. A total of 98 papers in 56 journals are identified. Three LSQ research focuses are identified. The review of the most frequently used dimensions of LSQ in different industries is made. The most appropriate and the most commonly used approaches for LSQ measuring are analysed. Most of the papers refer to empirical research and indicate the low level of LSQ. The review represents good basis of future researches, and also some kind of guidelines for practical application of LSQ in the field of transport and logistics.First published online 06 November 2019